Implementasi Arsitektur Biophilic Pada Fasilitas Club SPA Di Canggu, Kabupaten Badung, Bali: Bahasa Indonesia - Dewi Ratih Purnamasari; I Gede Surya Darmawan; Ida Bagus Gede Parama Putra (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2023)
One of the tourist facilities that can be developed in Canggu is SPA. The SPA industry is currently developing towards the achievement of physical, mind and soul health. The type of SPA chosen is Club SPA, because it offers SPA service facilities equipped with fitness facilities in order to get maximum results in physical and mental care, because nowadays people and tourists need a facility that can accommodate activities related to beauty, health, fitness, and relaxation to reduce the level of stress and depression, maintain, and improve physical and psychological appearance. The purpose of this research is to produce a Club SPA design concept with a biophilic architecture approach to produce a room that is able to improve physical and psychological health and create a positive relationship between humans and nature. The method used is by conducting literature studies, precedent studies, field observations, and surveys. The result of the research is the implementation of biophilic architecture that is applied to zoning, entrance, mass building, indoor space, outdoor space, and building facade. The implementation of biophilic architecture in the Club SPA design is expected to help the relaxation process by applying natural elements into the design.